Konsep Tanggung Jawab Kolektif dalam Akad Kafalah Analisis Tafsir Ahkam dan Aplikasinya di Era Modern - Alawiyah, Kiki Rofi'ah; Kamal, Asep Mustofa (Jurnal Hukum Ekonomi Syariah, 2025)
This study explores the concept of kafalah, or guarantee in Islam, from both traditional perspectives and its application in the modern era. The research problem addressed is how the understanding and implementation of the kafalah contract serve as one of the financial instruments in Islamic law, both theoretically and practically. The objective of this research is to examine the concept of kafalah according to Islamic jurisprudence, including its essential elements and conditions, legal basis, and its application in modern Islamic banking and insurance industries. This study employs a qualitative method with a literature review approach, analyzing primary sources such as the Qur'an, Hadith, and fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), as well as secondary sources such as books and academic journals. The findings indicate that kafalah in Islamic jurisprudence encompasses various forms, such as personal and financial guarantees, each with specific conditions and requirements. The essential elements (arkan) of kafalah include the offer and acceptance (ijab and qabul), the guarantor (al-kafil), the principal debtor (al-ashil), the creditor (al-makful lah), and the guaranteed obligation (al-makful bih). In the modern context, this concept is widely applied in Islamic insurance, credit guarantees, and other financial products that emphasize the principles of mutual assistance (ta’awun) and justice. Keywords: Kafalah; Guarantee; Islamic Jurisprudence; Islamic Banking; Islamic Insurance.